The effect of interactive speed training on the development of sensory-motor perception and volleyball reception skill for young women (Damu Journal of Sport Sciences, 2025)
The current study aimed to identify the effect of reactive speed training on developing sensorimotor perception and reception skills for young women's volleyball players at Al-Khalis Sports Club. The researcher used a single-group experimental approach with pre- and post-tests to suit the research problem. The research sample consisted of (13) young women's volleyball players at Al-Khalis Club, aged 15-17 years. (3) players were statistically excluded for non-compliance with the training sessions. The experimental group consisted of (10) players. The main experiment was conducted on the research sample for (6) weeks, with three sessions per week. After processing the results, the researcher reached the following main conclusions: Reactive speed training is highly effective in developing sensorimotor perception and reception skills in young women's volleyball. The most important recommendations were: The researcher recommends the need to consider reactive speed training in their training sessions to develop sensorimotor perception. and receiving skills.